International trade, intellectual property rights and the (un)employment of migrants - Lucas Guichard; Ignat Stepanok (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
We study the effect of trade liberalization and intellectual property rights (IPR) protection on the unemployment rate of migrants relative to non-migrants. We build a North-South trade and growth model with a positive steady state rate of migration. We find that bilateral trade liberalization decreases the relative unemployment rate of migrants when migration is low and increases the relative unemployment rate when the migration rate is high. The results do not rely on assumptions about network effects, the probability to find a job for a migrant is independent of the relative size of the migrant diaspora. IPR protection leads to a higher relative unemployment rate of migrants regardless of the size of migration. We empirically test and confirm the theoretical predictions on trade liberalization and IPR protection using data for 20 OECD (Organisation for Economic Co-operation and Development) countries over the period 2000-2014. – – Wir untersuchen die Wirkungen einer Handelsliberalisierung und des Schutzes geistigen Eigentums auf die Arbeitslosenquote von Migrantinnen und Migranten im Vergleich zu Einheimischen im Zielland. Die Analyse stützt sich auf ein Nord-Süd-Handelsmodell mit Wirtschaftswachstum und einer positiven Migrationsrate. Eine bilaterale Handelsliberalisierung führt zu einer niedrigeren Arbeitslosenquote von Migrantinnen und Migranten bei geringer Migration und zu einer höheren Arbeitslosenquote, wenn die Migrationsrate hoch ist. Dieses Ergebnis beruht nicht auf Netzwerkeffekten: Die Wahrscheinlichkeit eine Stelle zu finden ist unabhängig von der Größe der Diaspora. Ebenso führt der Schutz geistigen Eigentums zu einer höheren Arbeitslosenquote von Migrantinnen und Migranten unabhängig von der Größe der Diaspora. Die theoretischen Hypothesen des Modells wurden anhand von Daten aus 20 OECD Ländern in der Periode 2000-2014 empirisch getestet. Die empirischen Ergebnisse bestätigen die theoretischen Vorhersagen des Modells.
Keywords: F12; F16; F22; F43; J63; O34; 330; Migration; unemployment; trade liberalization; intellectual property rights; North-South trade